Concurrent chemotherapy with partial breast irradiation in triple negative breast cancer patients may improve disease control compared with sequential therapy - Rhome, Ryan; Wright, Jean; De Souza Lawrence, Lana; Stearns, Vered; Wolff, Antonio; Zellars, Richard (Frontiers in Oncology, 2023)
Purpose: To report outcomes on a subset of patients with triple negative breast cancer (TNBC) treated on prospective trials with post-lumpectomy partial breast irradiation and concurrent chemotherapy (PBICC) and compare them to a retrospectively assessed similar cohort treated with whole breast irradiation after adjuvant chemotherapy (WBIaC). Methods and Materials: Women with T1-2, N0-1 invasive breast cancer with ≥ 2mm lumpectomy margins were offered therapy on one of two PBICC trials. PBI consisted of 40.5 Gy in 15 daily 2.7 Gy fractions delivered concurrently with the first 2 cycles of adjuvant chemotherapy. The comparison cohort received WBI to a median dose of 60.7 Gy, (including boost, range 42.5 – 66 Gy), after completion of non-concurrent, adjuvant chemotherapy. We evaluated disease-free survival (DFS), and local/ loco-regional/ distant recurrence-free survival (RFS). We compared survival rates using Kaplan-Meier curves and log-rank test of statistical significance. Results: Nineteen patients with TNBC were treated with PBICC on prospective protocol, and 49 received WBIaC. At a median follow-up of 35.5 months (range 4.8-71.9), we observed no deaths in the PBICC cohort and 2 deaths in the WBIaC cohort (one from disease recurrence). With a median time of 23.4 (range 4.8 to 47) months, there were 7 recurrences (1 nodal, 4 local, 4 distant), all in the WBIaC group. At 5 years, there was a trend towards increased local RFS (100% vs. 85.4%, p=0.17) and loco-regional RFS (100% vs. 83.5, p=0.13) favoring the PBICC cohort. There was no significant difference in distant RFS between the two groups (100% vs. 94.4%, p=0.36). Five-year DFS was 100% with PBICC vs.78.9% (95% CI: 63.2 to 94.6%, p=0.08) with WBIaC. Conclusion: This study suggests that PBICC may offer similar and possibly better outcomes in patients with TNBC compared to a retrospective cohort treated with WBIaC. This observation is hypothesis-generating for prospective trials.